2011
DOI: 10.1016/j.jedc.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure provision and macroeconomic performance

Abstract: Behavioral di¤erences between economies where infrastructure is privately provided and where the government is the sole provider are examined in the context of a growing economy. The choice between private and public provision generates di¤erences in the private sector's ability to internalize capital utilization decisions and market prices along the equilibrium path. This in turn has a crucial impact on the e¤ects of …scal policy on resource allocation and welfare in each regime. If the government wants to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The effects of infrastructure productivity have been studied using economic models (Lakshmanan, 2011: 1-12). In some instances, behavioural approaches have been used to calculate the impact of infrastructure on national growth (Chatterjee & Mahbub Morshed, 2011: 1288-1306.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effects of infrastructure productivity have been studied using economic models (Lakshmanan, 2011: 1-12). In some instances, behavioural approaches have been used to calculate the impact of infrastructure on national growth (Chatterjee & Mahbub Morshed, 2011: 1288-1306.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternatively, there are behavioral approaches, with estimates of a cost or profit function including capital stock and taking account the differing characteristics of public versus private capital (Romp and de Haan, 2007;Chatterjee and Mahbub Morshed, 2011). Each approach has strengths and weaknesses but there is more consensus that public capital has an effect on economic growth (Chatterjee and Mahbub Morshed, 2011), with most of the debate over the causality and output elasticity or multiplier rather than the effect itself (Sturm, Jacobs and Groote, 1999). However, the overarching explanation as to what drives economic growth is the multiplier effect (Haughwout, 2002).…”
Section: Infrastructure and Economic Growthmentioning
confidence: 99%
“…The media and political figures often overestimate the economic power of the multiplier effects to result in faster output growth, which allows for increased public investment (Domański and Gwosdz, 2010;Chatterjee and Mahbub Morshed, 2011). Earlier studies found a relatively strong growth rate when increasing infrastructure investment, with a 1% increase in the public capital stock raising total factor productivity by up to 0.4%.…”
Section: Infrastructure and Economic Growthmentioning
confidence: 99%
“…Our framework can also be related to the literature on government versus private provision of public goods (see, e.g., Devarajan, Xie, and Zou ; Chatterjee and Morshed ). An important difference of these frameworks with ours, though, is that they do not consider either the possibility of parallel investments (public–private) which may interact with each other, or the issue of distribution.…”
mentioning
confidence: 99%